Well assuming that this would be a typical triangle, and not a right angle one, knowing that the sum of all sides adds up to 180 degrees, simply add all of the expressions and one value and make it equal to 180, and then solve for x.
(6x-1) + (X+14) + 20 = 180
6x - 1 + X + 14 = 160
7x - 1 + 14 = 160
7x + 13 = 160
7x = 147
X = 21.
Now solve for the angles by plugging in X.
A = 6x - 1 = 6(21) - 1 = 125 degrees
C = X + 14 = (21) + 14 = 35 degrees.
I believe these are the solutions.
Answer:im not sure sorry
Step-by-step explanation:
Answer:
Step-by-step explanation:
Incomplete question.
How do you evaluate: To evaluate an algebraic expression, you have to substitute a number for each variable and perform the arithmetic operations. In the example above, the variable x is equal to 6 since 6 + 6 = 12. If we know the value of our variables, we can replace the variables with their values and then evaluate the expression.
Z - 7 = 8
subtract 7 from both sides
z = 15
hope this helped!